Semantic human activity recognition: A literature review. Issue 8 (August 2015) - Ziaeefard, Maryam; Bergevin, Robert
Abstract This paper presents an overview of state-of-the-art methods in activity recognition using semantic features. Unlike low-level features, semantic features describe inherent characteristics of activities. Therefore, semantics make the recognition task more reliable especially when the same actions look visually different due to the variety of action executions. We define a semantic space including the most popular semantic features of an action namely the human body (pose and poselet), attributes, related objects, and scene context. We present methods exploiting these semantic features to recognize activities from still images and video data as well as four groups of activities: atomic actions, people interactions, human–object interactions, and group activities. Furthermore, we provide potential applications of semantic approaches along with directions for future research.